Annual Report on Exchange Arrangements and Exchange Restrictions 2006. (Annual Report on Exchange Arrangements and Exchange Restrictions; 2006, 2006)
The Annual Report on Exchange Arrangements and Exchange Restrictions (AREAER) has been published by the IMF since 1950. It is a unique publication based on a database maintained by the IMF that tracks exchange arrangements and foreign exchange systems for all member countries on an annual basis and also provides historical information on these. The introduction to the volume provides a summary of recent global trends and developments in the areas covered by the publication. Individual country chapters report exchange measures in place, the structure and setting of the exchange rate, arrangements for payments and receipts, procedures for resident and nonresident accounts, mechanisms for import and export payments and receipts, controls on capital transactions, and provisions specific to the financial sector. A separate section in each chapter lists changes made during 2005 and the first part of 2006. The AREAER draws on information made available to the IMF from a number of sources, including during official staff visits to member countries, and has been prepared in close consultation with national authorities. The information is presented in a tabular format.